Corrosion behaviour of heat threated carbon steel - Mohamad Zaki, Hamsah (2012)
This thesis aims to investigate the corrosion behavior of high carbon steel at difference types of heat treatment and investigate the corrosion rate at difference temperature of heat treatment. Normalizing, water quenching and oil quenching of heat treatment were applied to the samples at selected temperature. The temperatures chosen for the heat treatment are 980 ˚C, 1015 ˚C and 1050 ˚C. Structural and mechanical properties of non heat treated and heat treated samples were determined using Vickers Hardness Test, optical microscope, Scanning Electron Microscopy (SEM). A standard micro hardness tester, equipped with a Vickers indenter and an indentation load of 500 gf was used for surface hardness measurement. The change of hardness and microstructure of heat treated AISI 1070 before corrosion and after corrosion were also observed. Electrochemical polarization measurement of the heat treated AISI 1070 were carried out by using a potentiostat. The polarization measurement of the heat treated AISI 1070 was conducted in a 3.5 % Sodium Chloride solution (NaCl). It was observed that the corrosion potential of AISI 1070 at normalized were higher than oil quenched and water quenched. Heat treatment for AISI 1070 in the 3.5 % Sodium Chloride solution (NaCl) posses a similar characteristic but different corrosion potential. The polarization curves on heat-treated AISI 1070 reveal a similar characteristic. The highest corrosion rate is non-heat treated AISI 1070 (13.96 mmpy) and the lowest corrosion rate is water quenched AISI 1070 at 1050 ˚C (0.5148 mmpy).